2015
DOI: 10.1115/1.4031182
|View full text |Cite
|
Sign up to set email alerts
|

Off-Nominal Component Performance in a Supercritical Carbon Dioxide Brayton Cycle

Abstract: Bechtel Marine Propulsion Corporation (BMPC) is testing a supercritical carbon dioxide (sCO2) Brayton system at the Bettis Atomic Power Laboratory. The integrated system test (IST) is a simple recuperated closed Brayton cycle with a variable-speed turbine-driven compressor and a constant-speed turbine-driven generator using sCO2 as the working fluid designed to output 100 kWe. The main focus of the IST is to demonstrate operational, control, and performance characteristics of an sCO2 Brayton power cycle over a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(12 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Recuperator approach temperature difference (conservative value and can easily be achieved using commercial units) The efficiency of the sCO 2 Brayton cycle increases with increasing turbine inlet temperature. The assumed efficiency at each temperature considered in this study is presented in Table 3 [15,35,36]. Higher temperatures necessitate high performance materials in the power cycle and receiver to prevent degradation, thereby increasing component costs [15].…”
Section: Parameter Description Valuementioning
confidence: 99%
“…Recuperator approach temperature difference (conservative value and can easily be achieved using commercial units) The efficiency of the sCO 2 Brayton cycle increases with increasing turbine inlet temperature. The assumed efficiency at each temperature considered in this study is presented in Table 3 [15,35,36]. Higher temperatures necessitate high performance materials in the power cycle and receiver to prevent degradation, thereby increasing component costs [15].…”
Section: Parameter Description Valuementioning
confidence: 99%
“…Due to this, improving radial inflow turbine (RIT) performance is one of the major topics in both academic researches and industrial practices. Many institutions such as Sandia National Laboratory (SNL) [4,5], Bechtel Marine Propulsion Corporation [6,7] and Nuclear Power Institute of China [8] have investigated RIT performance through experiments. Other researchers, e.g., Zhou et al [9,10] and Unglaube et al [11] have conducted theoretical analyses or numerical simulations to clarify the flow mechanism in S-CO 2 RIT.…”
Section: Introductionmentioning
confidence: 99%
“…Linares et al [13] proposed a modification to RCBC that facilitate heat addition at a lower pressure to enable the use of conventional shell and tube heat exchangers in order to reduce the cost of the PHEX for CSP applications. Clementoni et al provided the steady-state [14], off-design [15] and transient [16] operational results of a 100kWe experimental facility at the Naval Nuclear Laboratory, USA. Clementoni et al [17] also reported the operational results of the test facility for different compressor inlet temperature (CIT).…”
Section: Introductionmentioning
confidence: 99%
“…Inventory control turndown is limited, however, by the size of the CO2 storage tank and the pressure pinch between that storage tank pressure and the system pressure. Although a bigger inventory storage tank can push the sCO2 cycle turndown ratio further, the optimal size is an economical trade-off between the CAPEX and improvement in annual energy generation [15].…”
Section: Introductionmentioning
confidence: 99%